Avaliação farmacocinética pré-clínica de candidatos a fármacos antituberculose - Dadda, Adilio da Silva (2018)
Tuberculosis (TB), caused mainly by Mycobacterium tuberculosis, is an infectious disease responsible for a significant number of deaths worldwide. IQG-607 is an analog of isoniazid (INH). According to several experiments carried out by our research group, IQG-607 showed both in vitro and in vivo anti-TB activity. Initial studies showed that the compound INCT-TB551 (a quinoline derivative) also presents in vitro anti-TB activity. The aim of this study was to develop analytical methods by high performance liquid chromatography (HPLC-UV) for quantification of IQG-607 and INCT-TB551 in mice plasma, and therefore to perform pharmacokinetic studies. The analytical method for the determination of IQG-607 in mice plasma showed linearity (r = 0.9992) in 0.5– 50 μg/mL concentration range. Intra- and inter-day precision was < 15%, and the recovery ranged from 92.07 to 107.68%, showing that the method provides a precise and accurate analysis of the compound. In addition, IQG-607 was stable in plasma for at least 30 days at −80 °C, and after plasma processing, for 4 h in the auto-sampler (6 ºC) and maintained on ice (recovery > 85%). The applicability of the method for pharmacokinetic studies was determined after intravenous (i.v.) and oral (fasted and fed conditions) administrations to mice. IQG-607 levels in plasma were quantified at time points for up to 2.5 h. A short half-life (t1/2) (1.14 h), a high clearance (CL) (3.89 L/h/kg), a moderate volume of distribution at steady state (Vdss, 1.22 L/kg), were observed after i.v. (50 mg/kg) administration. Similar results were obtained for oral administration (250 mg/kg) under fasted and fed conditions. The oral bioavailability (F), approximately 4%, was not altered by feeding. Plasma protein binding was 88.87 ± 0.9%. Recently, experiments in mice infected with M. tuberculosis have shown that the compound INCT-TB551 has no in vivo activity, unlike previous in vitro activity studies. An analytical method was developed for the determination of INCT-TB551 in mice plasma to assess compound absorption, if any, after oral administration. The analytical method presented linearity from 0.1-10 μg/mL (r = 0.9999). After development of the analytical method, the compound was orally administered in mice and the plasma levels were quantified at time points for up to 1 h. The compound INCT-TB551 was detected in the plasma of animals, which indicated that INCT-TB551 was absorbed. Although absorbed when orally administered, the compound is not exhibiting activity against M. tuberculosis in this animal model. This finding may be associated with the formation of inactive metabolites and/or the plasma concentration of INCT-TB551 achieved may be inadequate to exert its therapeutic effect. However, these points require further investigations. The protocols described here may serve as support to initiate pharmacokinetic studies of promising compounds, collaborating to advance in earlier stages of drug development.